Language and meaning in the age of modernism C.K. Ogden and his contemporaries - McElvenny, James (Edinburgh University Press, 2018)
James McElvenny explores the influential currents in the philosophy of language and linguistics of the first half of the 20th century, from the perspective of the English scholar C.K. Ogden (1889-1957). Ogden was connected to several of the most significant figures of the modernist period, including Bertrand Russell, Ludwig Wittgenstein, Victoria Lady Welby, Otto Neurath and Rudolf Carnap. In investigating these connections, McElvenny reveals links between early analytic philosophy, semiotics and linguistics in a crucial period of their respective histories and in turn sheds light on the intellectual history of the early 20th century.